2020
DOI: 10.3390/cancers12030762
|View full text |Cite
|
Sign up to set email alerts
|

Proposed Modification of Staging for Distal Cholangiocarcinoma Based on the Lymph Node Ratio Using Korean Multicenter Database

Abstract: The 8th American Joint Committee on Cancer (AJCC) staging system for distal cholangiocarcinoma (DCC) included a positive lymph node count (PLNC), but a comparison of the prognostic predictive power of PLNC and lymph node ratio (LNR) is still under debate. This study aimed to compare various staging models made by combining the abovementioned factors, identify the model with the best predictive power, and propose a modified staging system. We retrospectively reviewed 251 patients who underwent surgery for DCC a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 27 publications
0
11
1
Order By: Relevance
“…Whether age is an independent risk factor for DCC remains controversial. You et al ( 19 ) reported that age was significantly related to the prognosis of DCC, but Chen et al ( 30 ), Wu et al ( 31 ), and the results of this study reached the opposite conclusion. This may be due to the limitations of the different studies.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…Whether age is an independent risk factor for DCC remains controversial. You et al ( 19 ) reported that age was significantly related to the prognosis of DCC, but Chen et al ( 30 ), Wu et al ( 31 ), and the results of this study reached the opposite conclusion. This may be due to the limitations of the different studies.…”
Section: Discussioncontrasting
confidence: 82%
“…Regional LN metastasis is considered to be a key factor in evaluating the prognosis of patients after DCC (7)(8)(9)(10)17), but the effectiveness of the AJCC 8th edition N stage, as the latest and most commonly used stage, remains controversial (7,(17)(18)(19). Compared with AJCC 7th, AJCC 8th edition further subdivided N stage into N0 (PLNN = 0), N1 (PLNN = 1-3) and N2 (PLNN≥4) according to PLNN (11).…”
Section: Discussionmentioning
confidence: 99%
“…The LNR staging system combined with ELNN and PLNN compensates for the impact of insufficient ELNN on staging. A meta-analysis found that LNR = 0.2 is the ideal cutoff value for risk stratification of dCCA patients with radical resection ( 4 ), while the optimal cutoff value based on prognosis was between 0.45 and 0.17 ( 11 , 12 , 29 , 30 ). Similar cutoff values were obtained in our study by using X-tile software: LNR1-3: <0.1, 0.1 to 0.3, and ≥0.3.…”
Section: Discussionmentioning
confidence: 99%
“…Lymph node ratio (LNR), which is the ratio of PLNN to examined lymph node number (ELNN), has been proposed as an indicator of lymph node staging. Several studies have confirmed that the LNR is a promising indicator of the prognosis of dCCA (4,(9)(10)(11)(12). Log odds of positive lymph nodes (LODDS) is the log of the ratio of PLNN to negative lymph node number (NLNN).…”
Section: Introductionmentioning
confidence: 99%
“…However, the positive LNs factor was not included in the construction of the nomogram plot because the value of AIC was too large. AIC was considered as an important criterion for variable sieving and has been used in many studies 28,29 . Compared with our model, the TNM staging system earlier was not better for survival prediction, while our model was reasonable and logic by multivariate cox regression analysis and AIC algorithm which can prevent over tting of the model and ensure the accuracy of model 30 .…”
Section: Discussionmentioning
confidence: 99%